Drama Activities in a French Undergraduate Business School to Manage Speaking Anxiety in English - Privas-Bréauté, Virginie (SCENARIO: Journal for Performative Teaching, Learning, Research, 2019)
According to a study dated 2012 and led by the Confédération Française de l’Encadrement – Confédération Générale des Cadres (CFE-CGC) 2, many French executives feel stressed out when it comes to speaking English at work. An English teacher in a business school (undergraduate level), I am committed to preparing future actors of the professional world to better handle speaking English, so I introduce role plays and drama activities to help them feel less anxiety when they must speak English and prepare them to transfer it to their work place. This article will give an account of an experimentation I carried out through a pedagogical unit on "advertising" for third-year Business English students. I will analyze the interaction of body, emotions and mind along Varela’s “enaction” paradigm (1993, 1996) to show that drama games can foster students’ speaking skills development in English, and encourage transferable attitudes that can accompany speech and decrease anxiety.